Glycemic variability in patients with type 2 diabetes mellitus - I. A. Bondar; D. V. Grazhdankina; I. P. Krasnopevtseva (Лечащий Врач)
Background. Glycemic variability (GV) is a new risk factor for the development of vascular complications in patients with diabetes mellitus (DM). Clinical indicators associated with increased GV in patients with type 2 DM have not been sufficiently studied. Objective. To evaluate factors associated with increased GV in patients with type 2 DM.Materials and methods. We examined 88 patients with type 2 DM (mean age 55,3 ± 5,5 years, 65% women) with disease duration from 0,6 to 20 years. Ten patients with type 2 DM received only metformin (MF), 26 – MF in combination with sulfonylureas, 44 – insulinotherapy in combination with MF, and 8 – insulinotherapy. Patients with chronic kidney disease stages 3a-5, severe somatic pathology were excluded. GV was determined by calculating the standard deviation (SD) and coefficient of variation (CV) of glycemia, which was measured in the laboratory 3-4 times a day for 3 days. The relationship between CV and clinical and laboratory parameters and various glucose-lowering therapy regimens was searched for.Results. There was a positive correlation of CV with the duration of type 2 DM (rs = 0,28, p < 0,01), with the level of daily albuminuria (rs = 0,27, p = 0,011) and a negative correlation with the level of total cholesterol (rs = -0,26, p = 0,012) and low-density lipoprotein cholesterol (rs = -0,32, p < 0,01). There was no relationship between CV and age, body mass index, HbA1c, fasting and postprandial glycemic levels, estimated glomerular filtration rate, and insulin resistance indicators. A tendency towards an inverse correlation of CV with the level of C-peptide (rs = -0,24, p = 0,071) and insulin (rs = -0,25, p = 0,082) was revealed. CV was higher (p < 0,01) in patients with type 2 DM on conventional and intensive insulinotherapy (23,5% [19,3; 29,5] and 22% [20,1; 31,7], respectively) than on MF therapy (14,8% [9,8; 16,9]) or treatment of MF in combination with sulfonylureas (18,3% [14,8; 24,6]). CV > 36% was detected in 12 patients with type 2 DM and was associated with higher rates of daily albuminuria compared with CV < 36% (95 mg/day [55,8; 150] vs. 25,5 mg/day [11,5; 137,7], p =0,036).Conclusion. The main clinical factor associated with increased GV in patients with type 2 DM is the presence of microalbuminuria. An increase in glycemic fluctuations is detected in patients with type 2 DM on insulinotherapy more often than on treatment with MF in combination with sulfonylureas or MF monotherapy.